Identification of Albizia lebbeck seed coat chitin-binding vicilins (7S globulins) with high toxicity to the larvae of the bruchid Callosobruchus maculatus - A.J. Souza; A.T.S. Ferreira; J. Perales; D.G. Beghini; K.V.S. Fernandes; J. Xavier-Filho; T.M. Venancio; A.E.A. Oliveira (Brazilian Journal of Medical and Biological Research, 2012)
Seed coat is a specialized maternal tissue that interfaces the embryo and the external environment during embryogenesis, dormancy and germination. In addition, it is the first defensive barrier against penetration by pathogens and herbivores. Here we show that Albizia lebbeck seed coat dramatically compromises the oviposition, eclosion and development of the bruchid Callosobruchus maculatus. Dietary supplementation of bruchid larvae with A. lebbeck seed coat flour causes severe weight loss and reduces survival. By means of protein purification, mass spectrometry and bioinformatic analyses, we show that chitin-binding vicilins are the main source of A. lebbeck tegumental toxicity to C. maculatus. At concentrations as low as 0.1%, A. lebbeck vicilins reduce larval mass from 8.1 ± 1.7 (mass of control larvae) to 1.8 ± 0.5 mg, which corresponds to a decrease of 78%. Seed coat toxicity constitutes an efficient defense mechanism, hindering insect predation and preventing embryo damage. We hypothesize that A. lebbeck vicilins are good candidates for the genetic transformation of crop legumes to enhance resistance to bruchid predation.